PROGRAM DESIGN: CHALLENGES AND SOLUTIONS ROUNDTABLE - Finch, Chris (Sport- és Egészségtudományi füzetek, 2025)
There is a great emphasis on player development in short, medium, and long term. When the season is broken down into sets of five games, it is easier to set precise objectives, achieve improvement, and pay attention to every single game. In the league, there is a growing emphasis on load management and resting players, which can be seen as a status symbol for some team members. However, there is no scientific evidence to determine the value of resting, and it may send the wrong message to the team. In a league where every game matters, maintaining the mentality of winning the next game is crucial.